Dynamic spatial subchannel allocation with adaptive beamforming for MIMO - Ya-Han Pan (IEEE Transactions on wireless communications)
Orthogonal frequency division multiplexing (OFDM) has been widely regarded as an effective modulation technique for mitigating the effects of intersymbol interference in a frequency selective fading channel and for providing reliable high-data-rate transmission over wireless links. Adaptive antenna arrays at the base and mobile stations can achieve further increases in system's capacity and bandwidth efficiency, as well as in quality-of-service improvement in conventional OFDM systems. The conventional adaptive antenna-arrays-based OFDM systems always use the subcarriers characterized by the largest eigenvalues to transmit the OFDM block symbols. And in contrast to previous work, we propose dynamic spatial subchannel allocation with adaptive beamforming for broadband OFDM wireless transmission systems. The proposed system adaptively selects the eigenvectors associated with the relatively large spatial subchannel eigenvalues to generate the beamforming weights at the mobile and base stations and then dynamically assigns the corresponding best spatial subchannels to transmit the OFDM block symbols. It is shown that the proposed system can achieve better performance than an adaptive antenna-arrays-based OFDM system without dynamic spatial subchannel allocation over multipath fading channels. Simulation results also reveal that the proposed system is far less susceptible to feedback delay in rapid time-varying channels and a little more sensitive to channel estimation errors than conventional adaptive antenna-arrays-based OFDM systems. The performance of the proposed system combined with adaptive modulation is also considered.